How equitable are the distributions of the physical activity and accessibility benefits of bicycle infrastructure? - Christopher Standen; Melanie Crane; Stephen Greaves; Andrew T. Collins; Chris Rissel (International Journal for Equity in Health, 2021)
Abstract Background Cycling for transport provides many health and social benefits – including physical activity and independent access to jobs, education, social opportunities, health care and other services (accessibility). However, some population groups have less opportunity to reach everyday destinations, and public transport stops, by bicycle – owing in part to their greater aversion to riding amongst motor vehicle traffic. Health equity can therefore be improved by providing separated cycleway networks that give more people the opportunity to access places by bicycle using traffic-free routes. The aim of this study was to assess the health equity benefits of two bicycle infrastructure development scenarios – a single cycleway, and a complete network of cycleways – by examining the distributions of physical activity and accessibility benefits across gender, age and income groups. Methods Travel survey data collected from residents in Sydney (Australia) were used to train a predictive transport mode choice model, which was then used to forecast the impact of the two intervention scenarios on transport mode choice, physical activity and accessibility. The latter was measured using a utility-based measure derived from the mode choice model. The distributions of the forecast physical activity and accessibility benefits were then calculated across gender, age and income groups. Results The modelled physical activity and accessibility measures improve in both intervention scenarios. However, in the single cycleway scenario, the benefits are greatest for the male, high-income and older age groups. In the complete network scenario, the benefits are more equally distributed. Forecast increases in cycling time are largely offset by decreases in walking time – though the latter is typically low-intensity physical activity, which confers a lesser health benefit than moderate-intensity cycling. Conclusions Separated cycleway infrastructure can be used to improve health equity by providing greater opportunities for transport cycling in population groups more averse to riding amongst motor vehicle traffic. Disparities in the opportunity to access services and economic/social activities by bicycle – and incorporate more physical activity into everyday travel – could be addressed with connected, traffic-free cycleway networks that cater to people of all genders, ages and incomes.